DIAGNOSTICS OF CORPORATE SOCIAL RESPONSIBILITY OF ENTERPRISES IN THE CONTEXT OF ENSURING SUSTAINABLE DEVELOPMENT - GRECHAN, Alla; BILYK, Volodymyr (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Thearticle examines the diagnostics of corporate social responsibility (CSR) of enterprises as a tool for ensuring sustainable development, with a focus on transport companies. Modern approaches to assessing business social performance are analyzed, including analytical, sociological, expert, and computational methods. Special attention is given to the development and application of a system of indicators for CSR diagnostics, which allows for a comprehensive evaluation of the social, environmental, and economic impact of enterprise activities on stakeholders and the community. The importance of using tools such as SWOT, PESTEL, ESG metrics, and Balanced Scorecard to integrate social and economic indicators into strategic management is highlighted. The role of sociological surveys and expert evaluations in increasing transparency and humanization of business processes is emphasized. The study confirms that systematic CSR diagnostics and the use of indicators contribute to the formation of a transparent, responsible, and sustainable development–oriented enterprise strategy.